Una aproximación al conocimiento y la aplicación de la Ley que regula el Uso Legítimo de la Fuerza en Ecuador (Revista de Ciencias de Seguridad y Defensa, 2024)
This study explores the implementation of the new Law on the Legitimate Use of Force in Ecuador, which seeks to strengthen security procedures in the face of increasing violence in the country. The law aims to guarantee a proportionate and necessary use of force aligned with human rights principles. Through a survey of 103 officials, their perceptions on training, law enforcement, and inter-agency coordination were examined. The results show that most participants expressed strong agreement with the proper enforcement of the legal framework and willingness to abide by constitutional orders. However, gaps in knowledge of the law are evident that must be addressed through awareness campaigns, especially among young police officers who accounted for most of the sample. The need for motivational and awareness strategies on legal protection for security forces and citizens is highlighted. Therefore, the main objective of this research is to provide real and firsthand data about the reality faced by our security and defense officials in their daily practices. It also aims to examine their commitment to the Ecuadorian state and analyze the decisions made regarding the Legitimate Use of Force. While the law represents progress, its effective implementation requires greater training and internalization by its operators, as well as inter-forces coordination. The findings of this exploratory study provide insights into the initial application of the law and the perception of its key actors.